Penerapan Asean Ecotourism Standard di Edu-ekowisata Pengudang Bintan Mangrove Kabupaten Bintan - Indah Andesta (Yayasan Literasi Sains Indonesia, 2025)
Mangrove edu-ecotourism is a tourism practice that is responsible and sustainable. The practice is implemented through conservation activities in mangroves, the local communities', economic and social aspects. Pengudang Village applies the concept of mangrove edu-ecotourism. Mangrove edu-ecotourism practices must be in line with ecotourism practices that can be seen based on the criteria in the Asean Ecotourism Standard. This study uses a qualitative method, with data collection techniques including other observations, literature reviews and interviews. Data were analyzed using qualitative descriptive based on 65 criteria of the Asean Ecotourism Standard to determine the extent to which the results obtained from the assessments that have been carried out. Mangrove edu-ecotourism activities in Pengudang Village are related to mangrove tourism, bird watching, mangrove education, mangrove fireflies, and as a research center. All activities related to mangrove education have an impact on the local community in the form of knowledge related to mangroves and improving livelihoods in the tourism sector. Related to the mangrove edu-ecotourism activities assessed with the Asean Ecotourism Standard, the results are that there are 32 mandatory criteria that are met, 14 optional criteria that are met and 8 specific criteria that have been met in the Pengudang Village mangrove edu-ecotourism. The number obtained from the mandatory criteria with gold recognition in the Asean Ecotourism Standard. Improvements are needed in the mandatory criteria, namely service quality, in the optional criteria, namely the utilization of sustainability and service quality.